2022
DOI: 10.3390/diagnostics12071759
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papilloma Virus Infection in Bladder Cancer: A Systematic Review

Abstract: The etiology of bladder cancer is known to be associated with behavioral and environmental factors. Moreover, several studies suggested a potential role of HPV infection in the pathogenesis with controversial results. A systematic review was conducted to assess the role of HPV. A total of 46 articles that reported the prevalence of HPV infection in squamous (SCC), urothelial (UC), and transitional cell carcinomas (TCC) were selected. A pooled prevalence of 19% was found, with a significant difference in SCC th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 63 publications
1
18
0
1
Order By: Relevance
“…14 On the other hand, two recent meta-analyses have shown conflicting results, one showing that HPV infection is not associated with bladder cancer (OR: 2.077, 95% CI: 0.940-4.587), 6 while the other reported a significant association between HPV infection and bladder cancer (OR: 7.8406, 95% CI: 4.343-14.16). 15 However, condyloma acuminatum can develop into SCC. Samarska et al summarized 38 patients with condyloma acuminatum of the bladder, 17 of whom had SCC concurrently with condyloma acuminatum or within a year of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 On the other hand, two recent meta-analyses have shown conflicting results, one showing that HPV infection is not associated with bladder cancer (OR: 2.077, 95% CI: 0.940-4.587), 6 while the other reported a significant association between HPV infection and bladder cancer (OR: 7.8406, 95% CI: 4.343-14.16). 15 However, condyloma acuminatum can develop into SCC. Samarska et al summarized 38 patients with condyloma acuminatum of the bladder, 17 of whom had SCC concurrently with condyloma acuminatum or within a year of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity of HPV to differentiating squamous epithelium and the ability to evade immune responses may explain the mechanism of cancer development in the bladder epithelium. 15 A meta-analysis demonstrated that the association between HPV and bladder cancer risk was highest among Asians (OR 6.289; 95% CI 2.167-18.250). 6 In addition to geographical factors, age is also a risk factor for HPV-related cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Вместе с тем появились публикации, указывающие на влияние ВПЧ на течение РМП. Так, результаты опубликованного в 2022 г. метаанализа демонстрируют ухудшение прогноза течения РМП у ВПЧ-инфицированных пациентов [15], в другой публикации указана определенная этиологическая роль ВПЧ-инфицирования в развитии РМП [16]. В определенной степени сходное мнение высказывает другая группа исследователей [17].…”
Section: Introductionunclassified